Defining Physiology: Principles, Themes, Concepts Cardiovascular, Respiratory and Renal Physiology - Cheng, Hwee Ming (Springer Singapore, 2018)
This first volume of the book covers 150 important words and phrases encountered in cardiovascular, respiratory and renal physiology, elaborating the concepts, principles and common themes around these words. It offers students a quiver of arrows to direct their thinking accurately in order to understand targeted processes in physiology. Physiology teachers also find this 'definitive' physiology text useful in their lectures and tutorial classes to elaborate on homeostatic mechanisms in physiology. With any increase in physiological knowledge, there will be new words and terms that describe new mechanisms, and definitions of key words in core physiology are essential points of reference since they provide the foundational word pillars needed to understand physiology texts. This book is a valuable companion to the Springer series "Physiology-Question Based Learning (Pq-BL)" by the author. Both the questions and words for learning physiology well have been selected from the successful annual Physiology Quiz International event that is chaired and designed by the author.